Prioritizing project risks by a transdisciplinary approach using the grey ordinal priority approach: A case study of an electricity distribution company - Haghaniat, Saeedeh; Moosavirad, Seyed Hamed; Namjoo, Mohammad Reza (Transdisciplinary journal of engineering & science, 2024)
This paper addresses important concerns unique to network privacy in energy distribution systems by presenting a transdisciplinary framework that integrates transdisciplinary tools and transdisciplinary knowledge concepts from risk management, project management, electrical engineering and financial management. The study advances solutions that take into consideration both organizational and technical issues. This is achieved by combining effective decision-making approaches with real-world applications in electrical networks through the use of the Grey Ordinal Priority Approach (GOPA). Electricity distribution projects can immediately benefit from the comprehensive framework proposed by this study, which merges technical expertise with strategic risk management and offers useful insights that can be applied to a variety of domains. By emphasizing the importance of linking disciplines to effectively address complex, high-stakes project challenges, this transdisciplinary viewpoint enhances both the academic and practical dialogue. Results show that changes in project prioritization and announcement of new plans, pressure for early project delivery, improper selection of contractor and consultant, and lack of close supervision of project progress and scheduling are among the significant risks in the project. Electricity distribution companies can improve management of the complexity of their real-world projects by focusing on eliminating or reducing the severity of the aforementioned risks effects.